1970
DOI: 10.1111/j.1471-0528.1970.tb03524.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Value of Fetal Scalp Blood Sampling

Abstract: The value of fetal scalp sampling in reducing perinatal mortality, birth asphyxia and Caesarean section rate was assessed by a retrospective study of 2638 booked patients who were delivered in 1966. By using this technique it is possible that the perinatal mortality rate might be reduced from 15.9 to 15.2 per thousand, i.e., by 2 deaths per year. The incidence of birth asphyxia might be improved, but for this to be significant all patients would require repeated monitoring during labour, since about 40 per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1972
1972

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is concluded that foetal blood sampling is indicated in these types of cases. THE conventional clinical signs of foetal distress, namely the presence of meconium in the liquor amnii and changes in the foetal heart rate, have been shown to be not sufficiently reliable for the accurate assessment of the foetus (Wood & Pinkerton, 1961;Day, Maddern & Beard, 1968;Farr, 1970). Foetal blood sampling provides direct information about the foetal acid-base balance and gives a more accurate picture of the state of the foetus (Saling, 1966a).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that foetal blood sampling is indicated in these types of cases. THE conventional clinical signs of foetal distress, namely the presence of meconium in the liquor amnii and changes in the foetal heart rate, have been shown to be not sufficiently reliable for the accurate assessment of the foetus (Wood & Pinkerton, 1961;Day, Maddern & Beard, 1968;Farr, 1970). Foetal blood sampling provides direct information about the foetal acid-base balance and gives a more accurate picture of the state of the foetus (Saling, 1966a).…”
Section: Discussionmentioning
confidence: 99%